Inflammation mediates development of aggressive breast cancer following radiotherapy - Ma, Lin (Clin Cancer Res, 2021)
PURPOSE: Women treated with radiotherapy before 30 years of age have increased risk of developing breast cancer at an early age. Here we sought to investigate mechanisms by which radiation promotes aggressive cancer. EXPERIMENTAL DESIGN: The tumor microenvironment (TME) of breast cancers arising in women treated with radiotherapy for Hodgkin’s lymphoma was compared to that of sporadic breast cancers. We Investigated radiation effects on carcinomas arising from Trp53 null mammary transplants after irradiation of the target epithelium or host using immunocompetent and incompetent mice, some which were treated with aspirin. RESULTS: Compared to age-matched specimens of sporadic breast cancers, radiation-preceded breast cancers were characterized by TME rich in transforming growth factor β, cyclooxygenase-2 and myeloid cells, indicative of greater immunosuppression, even when matched for triple-negative status. The mechanism by which radiation impacts TME construction was investigated in carcinomas arising in mice bearing Trp53 null mammary transplants. Immunosuppressive TME (iTME) were recapitulated in mice irradiated before transplantation, which implicated systemic immune effects. In Nu/Nu mice lacking adaptive immunity irradiated before Trp53 null mammary transplantation, cancers also established an iTME, which pointed to a critical role for myeloid cells. Consistent with this, irradiated mammary glands contained more macrophages and human cells co-cultured with polarized macrophages underwent dysplastic morphogenesis mediated by interferon γ. Treating mice with low-dose aspirin for 6 months post-irradiation prevented establishment of an iTME and resulted in less aggressive tumors. CONCLUSIONS: These data show that radiation acts via non-mutational mechanisms to promote markedly immunosuppressive features of aggressive, radiation-preceded breast cancers.